Pengaruh Penggunaan Safety Glass Terhadap Gangguan Penglihatan Pada Pekerja Pengelasan Di PT. Jaya Teknik Indonesia Jakarta Selatan Tahun 2018 - Raditya Bagus Setiyaji; Revie Fitria Nasution (STIKes Persada Husada Indonesia, 2019)
Working accidents on welding can be prevented by using personal protective equipment (APD), each construction company is required to provide personal protective equipment (APD) for its workers, and ensure that the equipment is actually used by the welding worker. This study aims to analyze the effect of the use of safety glass to the impaired vision at PT Jaya Technique Indonesia. The sample in this research is welding workers at PT Jaya Technicque Indonesia in South Jakarta as many as 60 respondents. The sampling technique used accident sampling method. Data collection is done by distributing questionnaires and conducting direct interviews on PT projects. Jaya Technicque Indonesia. The method of analysis in this study using univariate analysis and bivariate analysis. Data processing is done by using SPSS with Chi Square analysis (x2). Based on the analysis, it is found that in the characteristics of health and long exposure in the use of safety glass has a positive or significant effect on the visual impairment. Likewise, the variable use of safety glass has a positive or significant effect on visual impairment. It can also be seen from the unsafe condition and unsafe action that both have a positive or significant effect on visual impairment. From the results of this study can be concluded that the use of safety glass (safety glasses) is very influential on the impaired vision of welding workers in PT Jaya Technicque Indonesia Year 2018.